Political women and American democracy - Wolbrecht, Christina (Cambridge University Press, 2008)
What do we know about women, politics, and democracy in the United States? The last thirty years have witnessed a remarkable increase in women's participation in American politics and an explosion of research on female political actors, and the transformations effected by them, during the same period. Political Women and American Democracy provides a critical synthesis of scholarly research by leading experts in the field. The collected essays examine women as citizens, voters, participants, movement activists, partisans, candidates, and legislators. The authors provide frameworks for understanding and organizing existing scholarship; focus on theoretical, methodological, and empirical debates; and map out productive directions for future research. Political Women and American Democracy is an invaluable resource for scholars and students studying and conducting women and politics research.